Respuesta :

By using the definition of inverse functions, we will see that:

g(g(f(f(f(36))))) = f(36) = 25.

What are inverse functions?

Two functions f(x) and g(x) are inverses if:

f( g(x) ) = x

g( f(x) ) = x

Then we can rewrite:

g(g(f(f(f(36)))))

First, we can see that:

g(f(f(f(36)))) = f(f(36))

Replacing that in our expression, we get:

g(g(f(f(f36))))) = g(f(f(36)))

And the above expression is equal to f(36), to be sure of that, let's replace:

u = f(36)

Then we can rewrite:

g(f(f(36))) = g(f(u))

And by definition, the above thing is equal to u:

g(f(u)) = u = f(36).

Finally, we conclude that:

g(g(f(f(f(36))))) = f(36) = 3*√36 + 7 = 3*6 + 7 = 25

If you want to learn more about inverse functions, you can read:

https://brainly.com/question/12220962